Separation and Characterization of Polyoheniloxidase (PPO) from Melissia Officinalis - Sabir, D.M. (Sulaimani Journal for Pure and Applied Sciences, 2000)
Polyphenol oxidase ( ppo) of Melissia officinalis was isolated and purified by gel filtration and ion exchange chromatography. Three isoenzymes were separated.The isoelectric points and some kinetic properties of these isonzymes are reported.